Remembering the Historic Jesus—A New Research Program? - Tilley, Terrence W. (Theological studies, 2007)
The article argues that a new research program is emerging, one that shifts the focus from the quests for the “historical Jesus,” a person in the past, to recovering the “historic Jesus,” the person remembered by his followers. It finds that Jesus' historic significance is and should be the center of Jesus research. It argues that the works of Elisabeth Schüssler Fiorenza, James D. G. Dunn, and Larry Hurtado are key contributions that indicate the shape of this research program.